Current Treatment Options for Fuchs Endothelial Dystrophy - Cursiefen, Claus; Jun, Albert S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides state of the art information on modern minimally invasive lamellar transplant techniques for Fuchs endothelial dystrophy (FED), such as Descemet stripping automated endothelial keratoplasty (DSAEK) and Descemet membrane endothelial keratoplasty (DMEK). In addition to clear step-by-step descriptions of procedures, guidance is offered on donor tissue preparation, potential intra- and postoperative complications, and complication management. Future treatment options in the form of medical, cell-based approaches are also discussed. To complete the picture, relevant information is included on the pathophysiology, clinical features, and differential diagnosis of FED. This book will be of interest to all who wish to learn about the dramatic developments in corneal transplantation and medical treatment that are transforming the management of FED.
Epidemiology and genetic basis of Fuchs Endothelial Corneal Dystrophy -- MicroRNAs in FED: New therapeutic option? -- Clinical phenotypes of Fuchs Endothelial Corneal Dystrophy (FECD), disease progression, differential diagnosis, and medical therapy -- Optical and anatomic changes in Fuchs Endothelial Dystrophy corneas -- Evolution of posterior lamellar keratoplasty: PK-DLEK-DSEK/DSAEK-DMEK-DMET -- DMEK Graft Preparation: eye bank perspective and risk factors for preparation failure -- Donor-tissue splitting and tissue storage for DALK and DMEK surgery -- DSAEK and UT-DSAEK in FED: Step-by-step approach -- DSAEK (not only) in Asian eyes: What glide to use? Optimized insertion techniques -- Intra- and postoperative complications and their management in DMEK -- DMEK: step-by-step surgical approach -- Complications of Descemet Stripping Automated Endothelial Keratoplasty (DSAEK) surgery -- Revision for failed penetrating keratoplasty in FED -- Long-term clear graft survival and chronic endothelial cell loss following posterior lamellar keratoplasty -- Immune reactions and dry eye after posterior lamellar keratoplasty -- Tissue engineering of a healthy corneal endothelium for FECD patients.
Keywords: Medicine; Ophthalmology; Minimally invasive surgery; Medicine & Public Health; Ophthalmology; Minimally invasive surgery